(3SDGdGJ Cgd GdnqQj Yf GdcdGe aj GdbQBf GdYRjRs - (3eMeO Hf GdWjH Hf eMeO Hf LYaQ, Jbj GdOjf CHh HcQ, GdbGVj GdHGbdGfj , J (B403 (3g` s
(3ChdgG (B:s
(3bGd GOGe Gddg YRg hSCdJe GMSf Gddg Jhajbce hef jeYf ajce s
(3BNQgG (B:s
(3hYdi Bdg hUMHg hSde hcGf GdaQGZ ef JYdjbg Sfg hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3Vef eLehYI dGdg dis
(3bUjOI dGejI eY TQMgG Ufag TjN eDjO GdLfjOi s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs